Uptake kinetics of five hydrophobic organic pollutants in the earthworm Eisenia fetida in six different soils - Šmídová, Klára; Hofman, Jakub (Journal of hazardous materials, 2014)
Hydrophobic organic contaminants in soils may pose toxicity or transfer to food chains after their uptake to soil biota. However, uptake data for earthworms are usually limited, as: (a) only fixed exposure times are studied instead of whole uptake kinetics and (b) studies including compounds with different environmental properties and more than two soils of different properties are quite rare. In our study, five persistent organic pollutants (phenanthrene, pyrene, lindane, p,p'-dichlorodiphenyltrichloroethane (p,p'-DDT), and polychlorinated biphenyl congener No. 153 (PCB 153)) were added to six soils of a wide range of soil properties. Detailed kinetics of uptake to earthworms Eisenia fetida were measured. Results indicated that an equilibrium of concentrations for p,p'-DDT and PCB 153 was reached after 11 days of exposure in all soils. Uptake of phenanthrene, pyrene, and lindane was strongly influenced by the decrease in concentrations in the soils, resulting in peak-shaped accumulation curves. Only in soils with the highest total organic carbon content (7.9 and 20.2%), the equilibrium of lindane concentrations was achieved (after 17 and 5 days of exposure, respectively). We recommend calculating bioaccumulation factors as a ratio of the uptake and elimination rate constants to precise the risk assessment.
Keywords: Organic Chemicals; DDT; Animals; Kinetics; Models, Statistical; Bioavailability; Polychlorinated Biphenyls; Insecticides; Soil Pollutants; Oligochaeta; polychlorované bifenyly; Polycyclic Compounds; látky znečišťující půdu; Hexachlorocyclohexane; statistické modely; Soil organic carbon; Earthworm; Bioaccumulation; Environmental Pollutants; insekticidy; organické látky; polycyklické sloučeniny; zvířata; Soil; látky znečišťující životní prostředí; půda; hexachlorcyklohexan; POPs; kinetika